ANALISIS TINGKAT KESEHATAN PT. BANK MUAMALAT INDONESIA, TBK DENGAN PENDEKATAN RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL (RGEC) - Iwan kusuma Negara (Master of Management, Mataram University, 2016)
This research aims to analyze the soundness level of PT. Bank Muamalat Indonesia, Tbk (PT. BMI, Tbk) measured by using Risk profile, Good corporate governance, Earning, and Capital (RGEC) approach in the period of 2009-2013. The type of research is applied research. The variables and measurements in this research consist of risk profile factor, good corporate governance factor, earning factor, and capital factor. The result of this research shows that the soundness level of PT. BMI, Tbk in the year of 2009-2013 by using RGEC approach on the whole can be classified as a healthy bank (PK 2). Risk profile factor which is measured by Non Performing Loan (NPL), Interest Rate Risk (IRR), Loan to Deposit Ratio (LDR), Loan to Asset Ratio (LAR), and Cash Ratio (CR) prove a well executed risk management. Good corporate governance factor indicates that PT. BMI, Tbk has had and applied corporate governance very well. Earning factor which is measured by Return On Assets (ROA), and Net Interest Margin (NIM) has increased, and this means the increasing of total assets owned by PT. BMI, Tbk that followed by increasing profit obtained by PT. BMI, Tbk. Capital factor which is measured by Capital Adequacy Ratio (CAR) proves that PT. BMI, Tbk has good capital, which is above the minimum requirement of Indonesian Bank i.e. 8 per cent.Keywords : Soundness Level, RGEC Approach, NPL, IRR, LDR, LAR, CR, ROA, NIM, CAR